2020
DOI: 10.1093/jac/dkaa419
|View full text |Cite
|
Sign up to set email alerts
|

Genetically related micafungin-resistant Candida parapsilosis blood isolates harbouring novel mutation R658G in hotspot 1 of Fks1p: a new challenge?

Abstract: Background Echinocandin resistance rarely occurs in clinical Candida parapsilosis isolates and the underlying mechanism is unknown. Objectives To determine the prevalence of echinocandin resistance and the underlying mechanism for a large collection of C. parapsilosis blood isolates and to determine whether the echinocandin-resistant isolates were clonally related. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 18 publications
2
32
1
Order By: Relevance
“…Of note, approximately 82% of CVC-recovered yeast isolates were C. albicans (9/ 11) ( Table 1 ), which also shows that other Candida species have the potential to cause CVC-related invasive yeast infections. Unlike endogenously acquired Candida species, such as C. glabrata , that require previous exposure to antifungals drugs to become drug-resistant, drug-resistant C. auris and C. parapsilosis can persist on the hospital environments, devices, and hands of healthcare workers and subsequently cause drug-resistant candidiasis and/or candidemia among antifungal-naïve patients [ 15 , 16 , 17 , 50 , 51 , 52 , 53 ]. It is also noteworthy that some studies have found an association between antibiotic use and the emergence of candidemia due to Candida species exhibiting a high minimum inhibitory concentration (MIC) and/or intrinsic resistance to fluconazole [ 54 , 55 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Of note, approximately 82% of CVC-recovered yeast isolates were C. albicans (9/ 11) ( Table 1 ), which also shows that other Candida species have the potential to cause CVC-related invasive yeast infections. Unlike endogenously acquired Candida species, such as C. glabrata , that require previous exposure to antifungals drugs to become drug-resistant, drug-resistant C. auris and C. parapsilosis can persist on the hospital environments, devices, and hands of healthcare workers and subsequently cause drug-resistant candidiasis and/or candidemia among antifungal-naïve patients [ 15 , 16 , 17 , 50 , 51 , 52 , 53 ]. It is also noteworthy that some studies have found an association between antibiotic use and the emergence of candidemia due to Candida species exhibiting a high minimum inhibitory concentration (MIC) and/or intrinsic resistance to fluconazole [ 54 , 55 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…parapsilosis blood isolates in Turkey, which harbored a novel amino acid substitution R658G in HS1-Fks1. These isolates were genetically related and resulted in caspofungin therapeutic failure in a patient infected with one of those isolates [ 157 ].…”
Section: Mechanisms Of Antifungal Resistancementioning
confidence: 99%
“…Candida parapsilosis is known to be susceptible to azole-class drugs; however, emerging studies have implicated the surge of clonal outbreaks as due to azole-resistant C. parapsilosis (ARCP) isolates in numerous countries [10][11][12][13][14][15], possibly fueled by azole overuse, which complicates the treatment of azole-naïve patients and is potentially associated with a higher mortality rate [16]. More alarming is the emergence of multidrug-resistant (MDR) C. parapsilosis isolates, resistant to both of the most widely used frontline antifungals, i.e., fluconazole and echinocandins [17], and the lack of effectiveness of these drugs against C. parapsilosis biofilms [18].…”
Section: Introductionmentioning
confidence: 99%